Growth of Vannamei Shrimp (Litopeneaus vannamei) in Rearing Media with Different Salinities - Scabra, Andre Rachmat; Junaidi, Muhammad; Hafizi, Auliyan (Jurnal Biologi Tropis, 2024)
The addition of calcium, phosphorus and magnesium minerals has been carried out separately in vannamei shrimp cultivation activities using fresh water media. Furthermore, the combination of the three types of potassium is expected to mutually fulfill the mineral needs of vannamei shrimp so that their growth becomes more optimal. This research aims to analyze the growth of vannamei shrimp reared in various media with different mineral levels. The treatments in this study were P1 (30 ppt), P2 (20 ppt), P3 (10 ppt), P4 (0 ppt without the addition of minerals), and P5 (0 ppt with the addition of various types of mineral sources). The research results show that the best SGR weight is found in P1 at 12.42%/day. The highest SR value was also obtained at P1, namely 65%. The SR and SGR values at P5 are higher than at P4, but still lower than at P1, P2, and P3. Based on these results, it is known that the growth of vannamei shrimp reared in fresh water media with added minerals has increased compared to vannamei shrimp reared in fresh water media without added minerals, but is still lower compared to the growth of vannamei shrimp reared in water media. sea. Furthermore, research is needed on adding other types of minerals to low salinity vannamei shrimp cultivation media.